2022
DOI: 10.1038/s41598-022-06868-3
|View full text |Cite
|
Sign up to set email alerts
|

Identification of candidate genes that specifically regulate subcutaneous and intramuscular fat deposition using transcriptomic and proteomic profiles in Dingyuan pigs

Abstract: Subcutaneous fat and intramuscular fat (IMF) deposition are closely related to meat production and pork quality. Dingyuan pig, as a native pig breed in China, low selection leads to obvious genetic and phenotypic differences in the population. Individuals with extreme fat content in the population are ideal models for studying the mechanism of fat deposition. In this study, we used RNA-Seq and tandem mass tags-based (TMT) proteomics to analyze the key pathways and genes that specifically regulate subcutaneous … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 61 publications
1
16
1
Order By: Relevance
“…Many genes regulate lipid droplet size and deposition. Forty candidate genes that may regulate fat deposition in subcutaneous and intramuscular fat were identified using transcriptomics in Ding Yuan pigs ( Zhang et al, 2022a ). In addition, based on transcriptomes of different breeds (Landrace pigs, Tibetan pigs, and Rongchang pigs) and tissues (SAT and VAT), Zhou et al (2013) suggested that subcutaneous adipose tissue differs from visceral and intermuscular adipose tissues due to lipid metabolism regulation ( Zhou et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many genes regulate lipid droplet size and deposition. Forty candidate genes that may regulate fat deposition in subcutaneous and intramuscular fat were identified using transcriptomics in Ding Yuan pigs ( Zhang et al, 2022a ). In addition, based on transcriptomes of different breeds (Landrace pigs, Tibetan pigs, and Rongchang pigs) and tissues (SAT and VAT), Zhou et al (2013) suggested that subcutaneous adipose tissue differs from visceral and intermuscular adipose tissues due to lipid metabolism regulation ( Zhou et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…FASN is associated with fat deposition in pigs and sheep ( Xing et al, 2021 ; Zhang et al, 2019 ; Zhao et al, 2022 ). Zhang et al (2022a) considered FASN a candidate gene for fat deposition. Another study showed a strong correlation between FASN and intramuscular fat ( Wang et al, 2020 ), and FASN determined lipid deposition using transcriptome and proteome data ( Wang et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Comparing gene expression between individuals with divergent traits in the same population can reduce noise owing to different genetic backgrounds [ 12 ]. In the present study, all pigs were selected based on the same breed, sex, and weight to allow candidate genes to be more dependable, thereby excluding unreliable factors identified owing to different breeds or different feed conditions.…”
Section: Discussionmentioning
confidence: 99%
“…As a polygenic trait, IMF is a complex metabolic process determined by the hyperplasia and hypertrophy of adipocytes and involves many biological processes and pathways, which are regulated by various molecules, such as hormones, transcription factors, protein-coding genes, and non-coding RNAs [ 10 , 11 , 12 ]. However, when compared with other traits, dissecting the genetic basis of IMF content is still limited, owing to its complexity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation